Data on compositional diversity of textural varieties of lake superior-type Banded Iron Formation (BIF) of the Njweng prospect, Mbalam iron ore district, southern CameroonMendeley Data - Dieudonne Charles Isidore Ilouga; Cheo Emmanuel Suh; Akumbom Vishiti; Elisha Muntum Shemang (Data in Brief)
In order to determine the nature of the original chemical precipitate and the ocean during the emplacement of BIF in the northern part of the Congo Craton data from the Njweng prospect anomaly was utilized. During field mapping and ground-truthing of this anomaly, samples were collected and the geochemical data of 26 representative samples constitute the core of this contribution. The selected samples for geochemical studies represented the various facies: oxide facies BIF composing of magnetite, hematite/martite, quartz; the silicate facies BIF composing of quartz, magnetite, hematite/martite and goethite. The ore (≥75 wt.% Fe) is a hematite-martite-goethite assemblage. The BIF show a characteristic banding and no association with volcanic activity. Chemical analysis was accomplished using a combination of the Inductively Coupled Plasma Emission Spectrometry (ICP-ES) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) on the major and trace elements respectively. The BIF have Fe2O3(T) content that ranges from 47.2 to 88.5 wt% and SiO2 from 1.87 to 49.28 wt% with the low silica content in the ore. The BIF show average SiO2 content of 41.20 wt% and 53.9 wt% Fe2O3. Both the oxide and silicate facies BIF samples show modern seawater characteristics (depletion in LREEY relative to HREEY, positive Eu(Eu/Eu*), Y anomalies and super chondritic Y/Ho ratios). The BIF reveals low Al2O3, TiO2, Na2O, K2O, HFSE and Nd concentrations. The average concentration of V, Ni, and Cu in the BIF is low.